Familia, redes y negocios en Sudamérica (1790-1850) - Viviana E. Conti (Nuevo mundo - Mundos Nuevos, 2008)
The article shows, how, during the whole life of a Spanish immigrant at the end of the 18th century, the accumulation of capital in relationships, made it possible for him to get a significant social and economic status, to access the local government and attain a good standard of living. Manuel de Tezanos Pinto was poor when he arrived to a receptive society of South America, without capital and prestige. However, he was able to build up social relations, based upon paisanaje and family, which allowed him and his family to access a higher level in the society. He passed on to his family not only a business based on his relational capital he gathered throughout his life, but also the necessary knowledge which his family applied in other fields.